Development of a Developmentally Appropriate Practice (DAP) model based on Toba Batak local wisdom to optimize six aspects of early childhood development - Panggabean, Eva Saryati (Lembaga Riset Mutiara Akbar, 2026)
Early Childhood Education (PAUD) demands the fulfillment of six aspects of child development holistically through learning practices that are appropriate to the child's developmental stage, individual uniqueness, and socio-cultural context. Developmentally Appropriate Practice (DAP) has been widely recognized as the main pedagogical framework in PAUD, but its application in Indonesia still tends to be generic and has not been systematically integrated with local wisdom. This article aims to develop a conceptual model of DAP based on Toba Batak local wisdom to optimize the six aspects of early childhood development. The study uses an integrative literature review approach by analyzing literature related to DAP, culture-based early childhood education, and Toba Batak cultural studies. The results of the study indicate that Toba Batak cultural elements, such as regional languages, traditional music and dance, traditional games, Dalihan Na Tolu values, and religious and family practices, have pedagogical potential that aligns with the principles of DAP and is able to stimulate all aspects of child development. This article produces a conceptual framework